Human resource management : rationalising managerial decisions - Benuyenah, Vic (Emerald points., 2024)
Human Resource Management: Rationalising Managerial Decisions provides a concise overview of current HRM practices, revisiting fundamental concepts and examining their contemporary applications. By showcasing compelling case studies from renowned organisations Human Resource Management brings readers up to speed with the latest trends in the field, including the application of data analytics, an increasingly crucial skill in HR practice. With author Vic Benuyenah's practical and academic background, Human Resource Management: Rationalising Managerial Decisions will better facilitate people involved in the teaching and learning of HR management at both undergraduate and postgraduate level, while its practical insights make it an indispensable companion for those seeking to navigate the complex terrain of HR management successfully.